Relief available in judicial review - Mokhtar, Khairil Azmin (2010)
Judicial review within Malaysian context has been defined as ‘the process by which the High Court exercises its supervisory jurisdiction over the proceedings and decisions of inferior courts , tribunals and other bodies or persons who carry out quasi-judicial functions who are charged with the performance of public acts and duties.’ 1 This jurisdiction was originally derived from the common law, and was exercised by the issue of the prerogative writs of mandamus, certiorari and prohibition, but is now conferred and regulated by statute and rules of court. Thus in Malaysia Administrative law is received and practised as part of the common law of England and by the authorisation of the Courts of Judicature Act 1964. Judicial review of civil causes or matters is governed by i. The Rules of the High Court (PU (A) 50/80) ii. The Specific Relief Act 1950 (Act 137) iii. Pursuant to the inherent powers granted to the courts under para 1 of the Schedule to the Courts of Judicature Act 1964....